2011
DOI: 10.1007/s12288-011-0059-1
|View full text |Cite
|
Sign up to set email alerts
|

Unfurling the Rationale Use of Platelet Transfusion in Dengue Fever

Abstract: Dengue fever and dengue haemorrhagic fever have emerged as a global public health problem in recent decades. The practice of platelet transfusion has been adapted into the standard clinical practice in management of hospitalized dengue patients. The exact indications and situations in which platelet have to be transfused may vary greatly. Blood components especially platelet concentrates due to their short shelf life are frequently in limited supply. Hence, appropriate use of blood is required to ensure the av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
15
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 8 publications
4
15
1
Order By: Relevance
“…In contrast to our study, Pallavi et al [9] noted higher percentages of dengue cases among children with the largest proportion in the age group of less than 10 years, while Ayyub et al [15] and Lye et al [16] noted preponderance in the age group of 20-40 years which was similar to our study. Male preponderance (Male-to-female ratio 2.4:1) in the present study was similar to that reported in other studies [17,18,19].…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…In contrast to our study, Pallavi et al [9] noted higher percentages of dengue cases among children with the largest proportion in the age group of less than 10 years, while Ayyub et al [15] and Lye et al [16] noted preponderance in the age group of 20-40 years which was similar to our study. Male preponderance (Male-to-female ratio 2.4:1) in the present study was similar to that reported in other studies [17,18,19].…”
Section: Discussionsupporting
confidence: 70%
“…In the present study, the whole spectrum of dengue infections including DF (89.6%), DHF (6.4%) and DSS (4%) was seen. In a study by Pallavi et al [9], which included 71 serologically confirmed cases of dengue, who were given platelet transfusion, 65 patients (91.5%) had DF, 4 patients (5.6%) had features of DHF and 2 patients (2.9%) had signs and symptoms of DSS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to our study, Pallavi et al reported that only 21 patients (6.12%) presented with haemorrhagic manifestations. 12 In 42 out of total 121 cases, patients though their platelet counts were 20,000/cu. mm and above, having not showed any bleeding manifestations or signs of sepsis, they were transfused with platelets.…”
Section: Resultsmentioning
confidence: 95%
“…The percentage of inappropriately transfused platelets in the studies conducted by Pallavi et al and Ahamed et al were found to be 36% and 56% respectively. 1, 12 Makroo also stated that many times the indications for prophylactic platelet transfusions were not according the guidelines as prescribed by WHO. Clinicians, because of intense social pressure and the so called dengue panic syndrome, demand for platelet transfusions though it is actually not needed.…”
Section: Resultsmentioning
confidence: 99%